Den svenska idrottspolitikens två sidor. Några reflektioner om statens stöd till idrotten och svensk välfärdspolitik - Norberg, Johan R. (Forum for Idræt, 2011)
Artiklen omhandler den svenske idrætspolitik og giver indblik i statens støtte til idrætten med paralleler til den generelle svenske velfærdspolitik. The article gives a characterization of Swedish sports policy in relation to Swedish welfare policies. The analysis is divided between two main lines. First, I argue that sport in several aspects can be seen as an integral part of Swedish welfare policy. Thereafter, I emphasize differences with the result that sport can also be described as a deviant and »unimportant« area of government policy, albeit with a remarkable ability to allocate public resources. Finally, I argue that the Swedish government’s sports policy in recent years lost much of its former character as a divergent »side-track« in Swedish welfare policies. Thus, sport has strengthened its position – but to the cost that sport as an area of government policy has become more traditional and predictable.